2016
DOI: 10.4283/jmag.2016.21.1.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Precipitate Element Addition on Microstructure and Magnetic Properties in Magnetostrictive Fe83Ga17alloy

Abstract: The <100> oriented Fe 83 Ga 17 alloys with various contents of NbC or B were prepared by directionally solidification method at the growth rate of 720 mm·h. With a small amount of precipitates, the columnar grains grew with cellular mode during directional solidification process, while like-dendrite mode of grains growth was observed in the alloys with higher contents of 0.5 at% due to the dragging effect of precipitates on the boundaries. The NbC precipitates disperse both inside grains and along the boundari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It is also possible to obtain the magnetization curve and hysteresis loop using a hollow square or other closed geometrical shape [8]. The effect of precipitate element addition on the magnetic properties of the magnetostrictive Fe 83 Ga 17 alloy was studied with ring samples: the results showed that the coercivity significantly increased with the addition of such elements [9]. Addition of boron caused undesirable deterioration of the magnetic properties of a permalloy, while the effects of magnesium and calcium on its magnetic properties were small [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to obtain the magnetization curve and hysteresis loop using a hollow square or other closed geometrical shape [8]. The effect of precipitate element addition on the magnetic properties of the magnetostrictive Fe 83 Ga 17 alloy was studied with ring samples: the results showed that the coercivity significantly increased with the addition of such elements [9]. Addition of boron caused undesirable deterioration of the magnetic properties of a permalloy, while the effects of magnesium and calcium on its magnetic properties were small [10].…”
Section: Introductionmentioning
confidence: 99%